Corrigendum to “Lousy chicks: Chewing lice from the imperial shag, Leucocarbo atriceps” - Leonardi, María Soledad (2018)
The authors regret an involuntary mistake in the specific determination of Pectinopygus turbinatus, where the correct name is Eidmanniella pellucida. As follow we present the revised taxonomic review for this species: Taxonomic review Arthropoda Insecta Phthiraptera Haeckel, 1896 Amblycera Kellogg, 1896 Menoponidae Mjöberg, 1910 Eidmanniella pellucida Rudow, 1869.Type host: Phalacrocorax capensis. Type locality: Hydra Bay, South Africa. Type specimen/s data: Neotype, ♀ slide N°1954–318, Natural History Museum, London, UK. Other hosts: King cormorant P. albiventer, European shag P. aristotelis, double crested cormorant P. auritus, guanay cormorant P. bougainvillii, great cormorant P. carbo, rough-faced cormorant P. carunculatus, black-faced cormorant P. fuscescens, red-legged cormorant P. gaimardi, Magellan cormorant P. magellanicus, pelagic cormorant P. pelagicus, Brandt's cormorant P. penicillatus, spotted cormorant P. punctatus and pied cormorant P. varius. Site of infestation: the entire body, more abundant under the wings. Remarks The genus was originally described by Kéler (1938) being the type species Menopon brevipalpe. In their review of Eidmanniella, Ryan and Price (1969) recognized the synonym within M. brevipalpe and E. pellucida. Rudow (1869) described M. pellucidum from the Cape cormorant, Phalacrocorax capensis. Ryan and Price also recognized the following synoyms: M. sigmoidale from Cape cormorants (Picaglia, 1885) and M. kuwani from the Brandt's cormorant, P. penicillatus (Kellog and Chapman, 1902). Eidmanniella pellucida was previously recorded in guanay cormorant from Chile (Sepúlveda et al., 1997). The present constitutes the first record for Argentina and a new host-parasite association.